Xx. Issue 4 (July 2018) - Unknown
Abstract : To reduce the water content of food stuffs and ingredients heat is used to drive moisture from the product. This is often an inefficient method, being extremely energy intensive. However, low temperature evaporation can significantly reduce running costs compared with other drying systems.